The Negro in France - McCloy, Shelby T. (Shelby Thomas), 1898-1973 (Book collections on Project MUSE., 1961)
This historical study examines the black experience in Metropolitan France from the 1600s to 1960. Shelby T. McCloy explores the literary and cultural contributions of people of color to French society -- from Alexandre Dumas to Rene Maran -- and charts their political ascension.